2019
DOI: 10.1007/s12020-019-01958-1
|View full text |Cite
|
Sign up to set email alerts
|

Selenium supplementation in the management of thyroid autoimmunity during pregnancy: results of the “SERENA study”, a randomized, double-blind, placebo-controlled trial

Abstract: Purpose Selenium is frequently in nutraceuticals for pregnancy, given its role on fertility and thyroid metabolism. However, most evidence rise from non-controlled studies. We aimed to evaluate the protective effect of selenium against thyroid autoimmunity during and after pregnancy. Methods A multicenter, randomized, double-blind, placebo-controlled trial was performed and promoted by the Young Italian Endocrinologists Group (EnGioI)-Italian Society of Endocrinology. Forty-five women with thyroiditis in pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 49 publications
4
51
0
3
Order By: Relevance
“…A number of recent clinical trials have demonstrated that selenium supplementation can reduce thyroid autoimmunity (Mantovani et al . ) and improve thyroid function (Negro et al . ; Mao et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent clinical trials have demonstrated that selenium supplementation can reduce thyroid autoimmunity (Mantovani et al . ) and improve thyroid function (Negro et al . ; Mao et al .…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent clinical trials have demonstrated that selenium supplementation can reduce thyroid autoimmunity (Mantovani et al 2019) and improve thyroid function (Negro et al 2007;Mao et al 2016) in pregnancy although the sample sizes have been perhaps too small to identify any significant reductions in pregnancy complication risk. Thus, additional studies are required to interrogate the relationship between selenium intake and complications of thyroid dysfunction in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The SERENA study, a multicenter, randomized, double-blind, placebo-controlled trial, organized and promoted by the Young Italian Endocrinologists Group (EnGioI)-Italian Society of Endocrinology, aimed to evaluate the effect of Se supplementation on AIT during and after pregnancy [65]. A significant reduction of TPOAb and thyroglobulin antibodies (TGAb) postpartum titer was observed in patients treated with SeMet (83 μg/day) [at PP: TGAb 20 IU/ml (11.59-52.60), p < 0.01; TPOAb 255.00 IU/ml (79.00-292.00), p < 0.01], while antibody titer rebound was reported in the placebo group.…”
Section: Se and Thyroid Autoimmunity During Pregnancymentioning
confidence: 99%
“…There is still a comparative dearth of adequately powered mechanistic and functional studies elucidating the wider implications of Se and selenoproteins in female fertility and reproduction [9,28]. Available evidence highlights that studies focusing on role of Se as an essential trace element in female reproduction are mainly focused on human pregnancy [30] and related complications such as pre-eclampsia [31], miscarriage and preterm birth [9,32], intrauterine growth restriction [33], small-for-gestational age newborns [34], pregnancy-induced hypertension [35], and pregnancy-related autoimmune thyroid disease [36]. Lower Se status and glutathione peroxidase 3 (GPX3) activity are shown to contribute in the progression of neoplastic diseases of female reproductive system including endometrial and ovarian cancers [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%